Application of DBS sampling in combination with LC–MS/MS for pharmacokinetic evaluation of a compound with species-specific blood-to-plasma partitioning. (August 2012) - Xu, Guifen; Chen, Jiyun S; Phadnis, Ruta; Huang, Tom; Uyeda, Craig; Soto, Marcus; Stouch, Brian; Wells, Mary C; James, Christopher A; Carlson, Timothy J
Background: Dried blood spot (DBS) sampling in combination with LC–MS/MS has been used increasingly in drug discovery for quantitative analysis to support pharmacokinetic (PK) studies. In this study, we assessed the effect of blood-to-plasma (B:P) partitioning on the bioanalytical performance and PK data acquired by DBS for a compound AMG-1 with species and concentration-dependent B:P ratio.Results: B:P partitioning did not adversely affect bioanalytical performance of DBS for AMG-1. For rat, (B:P ratio of 0.63), PK profiles from DBS and plasma methods were comparable. For dog, concentration-dependence of B:P ratio was observed both in vivo and in vitro . Additional studies demonstrated concentration-dependence of the compound's unbound fraction in plasma, which may contribute to the concentration-dependence of the B:P ratio.Conclusion: DBS is a promising sampling technique for preclinical pharmacokinetic studies. For compounds with high B:P ratio, caution needs to be applied for data comparison and interpretation between matrices.